2018
DOI: 10.1007/s00122-018-3060-3
|View full text |Cite
|
Sign up to set email alerts
|

A new leaf rust resistance gene Lr79 mapped in chromosome 3BL from the durum wheat landrace Aus26582

Abstract: A new leaf rust resistance gene Lr79 has been mapped in the long arm of chromosome 3B and a linked marker was identified for marker-assisted selection. Aus26582, a durum wheat landrace from the A. E. Watkins Collection, showed seedling resistance against durum-specific and common wheat-specific Puccinia triticina (Pt) pathotypes. Genetic analysis using a recombinant inbred line (RIL) population developed from a cross between Aus26582 and the susceptible parent Bansi with Australian Pt pathotype showed digenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 26 publications
0
44
0
3
Order By: Relevance
“…Seedling resistance, also known as all-stage resistance, confers resistance to only certain races (race-specific) with a high degree; however, a shift in the virulence of the pathogen population can easily overcome seedling resistance (Kolmer, 2005(Kolmer, , 2013. Lr72 (Herrera-Foessel et al, 2014), Lr76 (Bansal et al, 2017), and Lr79 (Qureshi et al, 2018) are some examples of genes for seedling resistance to LR reported recently. On the other hand, APR is normally detected after the seedling stages, confers resistance to multiple races (nonrace-specific), provides a moderate level of resistance, and has been found to be more durable (Kolmer, 1996(Kolmer, , 2013McIntosh et al, 1995).…”
Section: Genome-wide Association Study Of a Worldwidementioning
confidence: 99%
“…Seedling resistance, also known as all-stage resistance, confers resistance to only certain races (race-specific) with a high degree; however, a shift in the virulence of the pathogen population can easily overcome seedling resistance (Kolmer, 2005(Kolmer, , 2013. Lr72 (Herrera-Foessel et al, 2014), Lr76 (Bansal et al, 2017), and Lr79 (Qureshi et al, 2018) are some examples of genes for seedling resistance to LR reported recently. On the other hand, APR is normally detected after the seedling stages, confers resistance to multiple races (nonrace-specific), provides a moderate level of resistance, and has been found to be more durable (Kolmer, 1996(Kolmer, , 2013McIntosh et al, 1995).…”
Section: Genome-wide Association Study Of a Worldwidementioning
confidence: 99%
“…The most effective, economical, and environmentally sound means of controlling this disease is the deployment of resistant wheat cultivars. To date, formally designated leaf rust resistance genes have been catalogued at 76 loci (Lr1-Lr79;McIntosh et al 2013McIntosh et al , 2017Qureshi et al 2018). The release of cultivars with resistance based upon single major resistance genes leads to the emergence of pathotypes with matching virulence.…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 80 genes conferring leaf rust resistance derived from Triticum aestivum wheat cultivars, wild wheat, grass species, and durum wheat have been identi ed and designated as Lr1 to Lr79 [2]. Among them, only Lr9, Lr19, Lr24, Lr34, Lr37, Lr38, Lr46, Lr47, Lr51, Lr53, and Lr68 confer effective resistance to leaf rust currently.…”
Section: Introductionmentioning
confidence: 99%